Lung Adenocarcinoma Complicated By Hydropneumothorax And Pericardial Effusion With Impending Cardiac Tamponade: A Rare Case Report From A Rural Hospital In Ketapang Regency: english - Saputra, Gede Ardi; Kalua, Kesih; Willim, Herick Alvenus; Munthe, Eva Lydia (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2024)
Lung adenocarcinoma is often associated with pulmonary complications such as hydropneumothorax and pleural effusion, and cardiac complications such as cardiac tamponade and pericardial effusion, but are very rare. In our case, a 52-year-old woman presented with worsening shortness of breath for 1 month. The patient underwent thoracentesis after chest X-ray showed right pleural effusion. Pleural fluid cytology showed pulmonary adenocarcinoma. Chest CT scan showed hydropneumothorax and pericardial effusion. In conclusion, pleural effusion is common in lung malignancies. In this case, hydropneumothorax occurred due to repeated thoracentesis of massive pleural effusion. Pericardial effusion is uncommon. This is due to the presence of metastases in the pericardium that obstruct lymphatic drainage, so pericardial fluid analysis is needed.